LMO4 is Required for Central Leptin Control of Fat Metabolism and Insulin Sensitivity. - Zhou, Xun (Université d'Ottawa / University of Ottawa, 2011)
Metabolic homeostasis is orchestrated by the hypothalamus through the neuroendocrine and the autonomic nervous systems. The hypothalamic nuclei respond to the peptide leptin secreted from adipose tissue to suppress feeding and increase energy expenditure by promoting fat metabolism via sympathetic activity. Another important, but perhaps less appreciated function of central leptin signaling is to elevate peripheral insulin sensitivity. Environmental and genetic risk factors that affect hypothalamic leptin signaling can lead to obesity and type 2 diabetes mellitus (T2DM). Here, we discovered that LIM domain only 4, LMO4, is a novel protein participating in central leptin signaling. In a process strikingly similar to T2DM in humans, CaMKIIα-Cre;LMO4flox/flox mice, which have LMO4 knocked out in the postnatal brain including the hypothalamus, develop visceral adiposity, reduced insulin sensitivity, obesity and diabetes when fed with regular chow. Central leptin signaling was significantly lost in key hypothalamic nuclei of mutant mice. Caloric restriction prevents obesity but not insulin resistance in these mice. Taken together, our results suggest that LMO4 function in the brain is required for central leptin signaling to control fat metabolism and peripheral insulin sensitivity.
Keywords: LMO4; leptin; adiposity; sympathetic outflow; insulin